Clinicopathological study of masses of nasal cavity and paranasal sinuses and its correlation with radiology - Soumya Sahu; Garima Malpani; Amit V. Varma; Kamal Malukani; Bela Sharda (MGM Journal of Medical Sciences)
Background: Nasal and paranasal abnormalities frequently represent the primary observations in the otorhinolaryngology domain. Thorough clinical evaluation and radiological methodologies aid in establishing a preliminary diagnosis; however, histopathological examination (HPE) remains indispensable for confirming a definitive diagnosis. The objective is to determine the demographic breakdown of patients exhibiting sinonasal lesions and to evaluate and correlate clinical and radiological observations with histopathological diagnoses. Materials and Methods: This ambispective observational study involved 128 sinonasal lesions diagnosed via histopathology spanning 3 years (2020–2023). All pertinent clinical radiological observations were recorded, and tissue samples underwent staining with hematoxylin and eosin (H&E), special stains, and immunohistochemistry (IHC) when necessary. The collected data were organized into tables, and statistical analyses were conducted. Results: Among the 128 cases examined, 98 (76.56%) were identified as non-neoplastic lesions, 14 (10.93%) as benign neoplasms, and 16 (12.50%) as malignant lesions through HPE. The male-to-female ratio stood at 1.2:1. The highest number of cases was observed within the age bracket of 21–40 years. Nasal obstruction emerged as the predominant symptom, accounting for 46 (35.93%) cases. Conclusion: A broad range of lesions can impact the sinonasal tract. While clinical and radiological characteristics may exhibit similarities, histopathology is the ultimate standard for confirming a definitive diagnosis.